(untitled) (Research, Society and Development, 2025)
Objective: To analyze the role of nurses in palliative care for the elderly population, identifying the challenges faced and the contributions to comprehensive care for elderly people at the end of life. Methodology: this is a qualitative-quantitative, cross-sectional study of the integrative literature review (RIL) type. The search took place in October 2024, using the Scientific Electronic Library Online (SciELO), CAPES Periodicals and Virtual Health Library (BVS) databases, complete original articles from the last 6 years available in the databases, in Portuguese, English and Spanish, and that are related to the theme. Result: Through the research carried out, 8 studies were found that addressed the aforementioned theme, exposing the main studies that demonstrate nursing assistance in palliative care in the elderly population. Conclusion: This research concluded that palliative care is essential for elderly patients, since, when provided by the nursing team, it becomes essential for the recognition and legitimization of the profession, highlighting the coordinating and humanized potential of the profession and, although it has gaps and challenges, it is extremely important for the actions instituted in palliative care.